Democracy and economic growth in an interdependent world - Mamata Parhi (Review of International Economics, 2013)
A spatial vector autoregression framework is set up to examine the dynamics of interdependence between democratic distance among countries and their long-run growth processes. We focus on (both geographic and relational attributes of) democratic distribution and find evidence of significant dynamic spatial autocorrelation among countries' growth processes indicating the existence of high degree of complementarity. Our estimation of a convergence-pattern framework also provides new insights into the likely impact of democracy on economic growth over decades. We find that democracy has exerted persistent growth-enhancing effect since 1970 where the democratic distribution has steadily shifted from low-level equilibrium to high-level equilibrium. Finally, it is demonstrated that the relevance of geographical proximity in facilitating interdependence in economic growth is overshadowed by relational proximity represented by democratic distance. Our results hold interesting policy implications.